Performance of Anticyclic Citrullinated Peptide Antibodies versus Rheumatoid Factor in diagnosis of Rheumatoid Arthritis - Ibrahim Ali , Ali; Jasim, Mohammed (Diyala Journal of Medicine, 2019)
The aim of this study was to evaluate the performance of anti-cyclic citrullinated peptide antibodies (anti-ccp) versus Rheumatoid Factor (RF) in the diagnosis of rheumatoid arthritis in serum sample of patients with clinical manifestation of arthritis using ELISA technique. One hundred and twenty patients with clinical presentation of rheumatoid arthritis and fifty apparently healthy individuals (25 males and 25 females) were enrolled in this study. The mean age of patients group and control was 36.45years versus 34.72 years .Among patients, males represented (8.3%) compared with (91.7%) of females. In control group males represented (52%) versus (48%) females. There was a statistical significant difference (p>0.05) between patients and control group in RF and anti-ccp values. Eighty five percent of patients gave positive results for anti-ccp compared with (100%) negative results in control group. RF was detected in (41.66 %) of patients sera compared with (58.33 %) which gave negative results. RF ELISA gave negative results in (100%) of control group . Only 10(8, 33%) out of 120 patients gave negative results in RF and anti-ccp ELISA, compared with 42(35%) out of 120 gave positive results in both tests. In 60(50%) out of 120 RA patients RF gave negative results and at the same time gave positive results when retested using anti-ccp ELISA .Only 8(6.66%) out of 120 RA patients gave negative result in anti-ccp ELISA technique and RF was detected in positive value. The sensitivity of anti-ccp ELISA was (85%) versus (41.66%) for RF. The Specificity of anti-ccp ELISA was (55.55%) versus (14.28%) for RF. Positive predictive value for anti-ccp ELISA was 41.17% versus (84%) for RF. Negative predictive value for anti-ccp ELISA was 55.55% versus 14.28 for RF ELISA .False positive value in anti-ccp ELISA was 58.82% versus 16%for RF ELISA. False negative value in anti-ccp ELISA was 44.44% versus 85.71%for RF . This study concludes that anti-ccp ELISA was more sensitive and specific in diagnosis of RA than RF ELISA technique.